Analisis faktor-faktor yang mempengaruhi kunjungan wisatawan nusantara asal Kota Jambi ke objek wisata alam Taman Nasional Kerinci Seblat (TNKS) di Kabupaten Kerinci Provinsi Jambi (pendekatan biaya perjalanan travel cost approach) - Cintya Anita; Muhammad Safri; Nurhayani Nurhayani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2019)
The purpose of this study to determine the development of visiting archipelago tourists from Jambi City to TNKS, factors that influence, and willingness to pay. The data used are secondary from BPS and primary data from questionnaires and direct interviews with a sample of 39. The sampling methods used was purposive sampling. The data an analysis tools are used is descriptive and quantitave analysis’s with multiple linear analysis. The resulth of this study indicate, the average development of tourists visiting the archipelago is 24,82%, the average hotel rates is 5,70%, the average number of private vehicles in Jambi City is 22,64%, the average productive populasi of Jambi City is 1,8%. The simultaneous all variables have a positive and signifikan effect. While partially the average hotel rates in Kerinci has a negative and insignificant effect, while the number of private vehicles in Jambi City and productive populasi of Jambi City have a positive and significant. Willingness to pay/WTP recorded at Rp. 4.026.375,- with an average of Rp. 2.647,- per person. Keywords: Average Hotel Rates, Number of Private Vehicles, Productive Population, Number of Nusantara Tourist Visits (WTP).